2011
DOI: 10.1002/sce.20464
|View full text |Cite
|
Sign up to set email alerts
|

Science education and test‐based accountability: Reviewing their relationship and exploring implications for future policy

Abstract: Assuming that quality science education plays a role in economic growth within a country, it becomes important to understand how education policy might influence science education teaching and learning. This integrative research review draws on Cooper's methodology (Cooper, 1982;Cooper & Hedges, 2009) to synthesize empirical findings on the relationship between science education and test-based accountability policies. Current accountability policy, particularly at the federal level, is intended to influence ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 37 publications
3
48
0
Order By: Relevance
“…However, it is perplexing to consider that a school's assessed quality had no correlation with the success of students in Regents Physics. Perhaps schools were directing resources towards remedial coursework and programs that would bolster graduation rates, a common outcome of test-based accountability policies [16]. Regardless, the assessment systems in place need to be realigned so student success in physical science coursework is acknowledged and rewarded.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is perplexing to consider that a school's assessed quality had no correlation with the success of students in Regents Physics. Perhaps schools were directing resources towards remedial coursework and programs that would bolster graduation rates, a common outcome of test-based accountability policies [16]. Regardless, the assessment systems in place need to be realigned so student success in physical science coursework is acknowledged and rewarded.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of 49 American studies, Au (2007) found that the main effect these types of tests have is that educational content is limited to what is tested, the subjects are fragmented into test-related pieces, and teachers increase their use of teacher-centred pedagogy. In the same vein, Anderson (2012) found in his research review that science instruction often was narrowed because of the pressure for accountability and that teachers' teaching practices became more fact-based. Another consequence was that teachers became less satisfied with their teaching and that many students' needs were not met.…”
Section: The Swedish School System and The Curriculummentioning
confidence: 94%
“…In a US context, Au (2011) describes the development of the school system as being regulated by efficiency improvements, such as standardised tests, that govern the details and reduce the professionals' opportunities for selecting and reflecting on content. Worldwide, testing continues to increase, even though research on the effects of high-stakes tests does not necessarily show improved student learning outcomes (Anderson 2012).…”
Section: The Swedish School System and The Curriculummentioning
confidence: 99%
“…Scientific organizations such as the American Association for the Advancement of Science (AAAS), the National Research Council (NRC), and the National Science Foundation (NSF) promote student-centered pedagogies such as inquiry, constructivism, and project-based learning as ways to increase student engagement and achievement in science (Anderson, 2012). While K-12 teachers, principals, and administrators express superficial support for these reform efforts, improving student scores on standardized tests often takes precedence in the classroom.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When No Child Left Behind was in place, technically speaking, only reading and math scores were truly "high stakes," as schools and districts whose students did not make Adequate Yearly Progress in those subjects could be subject to negative sanctions. However, science teachers also perceived their students' publicly available standardized test results to be high stakes, which in turn reinforced a "teach to the test" mentality (Anderson, 2012). In addition, many states have high school graduation tests which include a section on science.…”
Section: Literature Reviewmentioning
confidence: 99%